Giving Contents From an Unlabelled Plastic Bottle Containing Toxic Substance: A Case Report - Lakshmi Shobhavat; Manoj Parchake; Shankar Subramanian; Harish Pathak; Nilesh Tumram; Avinash Shelke (Arab Journal of Forensic Sciences & Forensic Medicine, 2022)
Accidental exposure to toxic chemicals is a major concern for all of us, particularly for our children. Many households in different parts of the globe store chemicals/drugs right from medicine, toiletries, corrosives, etc. in bottles of various sizes, shapes, and substances. Many a time such bottles are either newly purchased or are empty bottles of previously-stored liquids or other contents. Such used bottles or containers are frequently used for preserving corrosives or household cleaning substances in homes. Such unlabelled or used bottles can become culprits for causing accidental poisoning to anyone, especially children leading to grave harm to their health and safety.